33.1: Invited Paper: Multi‐plane Display Based on Cholosteric Liquid Crystal Films. (4th October 2019) - Chen, Quanming; Peng, Zenghui; Li, Yan; Liu, Shuxin; Zhou, Pengcheng; Gu, Jingyuan; Lu, Jiangang; Yao, Lishuang; Wang, Min; Su, Yikai
Abstract : In this paper, we present a multi‐plane augmented reality display based on polarization multiplexing. With reflection selectivity of cholesteric liquid crystal (CLC) films, left‐handed and right‐handed circularly polarized images are imaged at different depths. Monocolor and color dual‐plane display experiments have been implemented and verified to provide correct depth cues.